DigiPal: Digital Resource and Database of Palaeography, Manuscript Studies and Diplomatic. - MAGNI, ISABELLA (Renaissance & Reformation / Renaissance et Réforme)
The article reviews the website DigiPal located at digipal.eu. developed by web developers at the Department of Digital Humanities at King's College in London, England for the study of medieval handwriting.